2010
DOI: 10.1186/1748-717x-5-93
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical experience with volumetric modulated arc therapy in head and neck cancer patients

Abstract: Background: To report about early clinical experience in radiation treatment of head and neck cancer of different sites and histology by volumetric modulated arcs with the RapidArc technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 28 publications
2
25
0
5
Order By: Relevance
“…Preliminary data suggests that acute toxicity with VMAT in head and neck cancer is acceptable. Scorsetti et al [101] reported 45 patients who were treated with VMAT (RapidArc, Varian), of which 78% also received concomitant chemotherapy. In their patient series, the incidence of NCI CTCAE v.3.0 Grade 3 mucositis was 28%, Grade 3 dermatitis was 14% and Grade 2 dysphagia was 44%.…”
Section: Head and Neck Cancermentioning
confidence: 99%
“…Preliminary data suggests that acute toxicity with VMAT in head and neck cancer is acceptable. Scorsetti et al [101] reported 45 patients who were treated with VMAT (RapidArc, Varian), of which 78% also received concomitant chemotherapy. In their patient series, the incidence of NCI CTCAE v.3.0 Grade 3 mucositis was 28%, Grade 3 dermatitis was 14% and Grade 2 dysphagia was 44%.…”
Section: Head and Neck Cancermentioning
confidence: 99%
“…More refined radiation techniques, which lead to enhanced conformity, can be performed with the use of these generation machines. 3-D techniques have given way to IMRT or volumetric modulated arc therapy (V-MAT) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the RapidArc TM technique provoked effects in mucosa only in week 6. Patients from both treatment techniques were also undergoing combined treatment with chemotherapy, which could have influenced the toxicity increase in the normal tissues 10,18,5,6 . With regards to the salivary glands results, we have observed that all IMRT patients demonstrated effects in the 4 th week of treatment, with some patients experiencing high-degree effects.…”
Section: Scorsetti and His Group In 2010 Initiated A Clinical Experimmentioning
confidence: 99%
“…A prescrição da dose necessĂĄria para o tratamento Ă© baseada em diversos fatores, nomeadamente na localização, no tipo de lesĂŁo, no intuito do tratamento, no facto de ser combinada com outras modalidades de tratamento, entre outros. Quando o intuito Ă© curativo, as doses podem variar entre os 50 Gy e os 70 Gy, perfazendo um tempo total de tratamento de 5 a 7 semanas, em esquemas de fracionamento convencional (1,8 Gy/ d a 2 Gy/ d) ou em esquemas alterados de fracionamento 18 . Os rĂĄpidos avanços nas tĂ©cnicas de Radioterapia permitem uma poupança considerĂĄvel dos tecidos normais, no entanto, a maioria dos doentes tratados com doses curativas desenvolverĂŁo efeitos agudos ao tratamento, o que requererĂĄ a intervenção de um apoio multidisciplinar especializado.…”
unclassified
See 1 more Smart Citation